The Ethical Challenges in Copyright AI Creativity: Tantangan Etis dalam Kreativitas AI Hak Cipta - Putri, Tasya Raehan Annisa; Disemadi, Hari Sutra; Hutauruk, Rufinus Hotmaulana (Fakultas Hukum Universitas Tompotika Luwuk Banggai, 2025)
In this era of rapid technological advancement, marked by the emergence of Artificial Intelligence (AI), the legal status surrounding AI-generated works sparks considerable debate. The question arises: do these creations warrant legal protection? This study employs a normative legal research method, drawing upon statutory regulations. Findings indicate that AI cannot be deemed a legal subject with rights and obligations, as it is a product of human-made technology. Consequently, AI-generated works do not meet the criteria for copyright protection, namely fixation, originality, and minimal creativity. Indonesia addresses copyright protection under Law Number 28 of 2014, stipulating that AI-generated works can be protected through registration, provided they meet standards of originality and human creative contribution. This essentially renders AI creations ineligible for legal protection, as they originate from machine intervention. However, legal protection for AI can be circumvented by directing it towards the owner and creator of the AI itself, rather than its resultant works.